Uruguay : Sixth Review Under the Stand-By Arrangement and Requests for Modification of the Arrangement, Waiver of Nonobservance and Applicability of Performance Criteria, and Extension of Repurchase Expectations in the Credit Tranches-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper examines Uruguay's Sixth Review Under the Stand-By Arrangement and Requests for Modification of the Arrangement. The macroeconomic framework is on track, but progress with structural reform remains uneven. Fiscal performance has been better than programmed, reflecting buoyant revenues. The monetary and balance-of-payments targets of the program are being met as well. GDP growth is now forecast at 11 percent in 2004. The restructuring of the public banks and disposal of assets in the bank liquidation funds are moving forward.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet